KAJIAN SKALA PADA BANGUNAN TRADISIONAL ANGKOLA (Studi Kasus : Museum GKPA, Silangge) - Sitanggang, Fernanda; Silitonga, Shanty; Napitupulu, Putri P (Unika Santo Thomas, 2019)
This research raises the scale study of traditional angkola buildings with a case study of the GKPA Museum, Silangge. This building consists of the elements making up the space, both indoor and outdoor. The building blocks in the building include: the head of the building (ni orbo horns, closed capillaries, dadap na tolu, and lisplank), the building body (doors, windows, vents, and poles), and the legs of the building (foundations, columns, and stairs). While the building elements outside the building include: buildings with supporting functions (Debora orphanage and Debora orphanage study room), Debora orphanage field, and some vegetation around the Angkola Museum. The scale that will be examined in this study is the human scale (human as a benchmark) of the elements forming the outer space of traditional Angkola buildings. The scale study will be carried out by analyzing the human scale of the building with a predetermined observation point. This study was classified in research that uses descriptive methods with qualitative analysis. Data analysis with descriptive analysis techniques that use benchmarks. Evaluation research that aims to assess the extent to which the variables studied are in accordance with predetermined benchmarks. The benefit of this research is finding a scale study found in Angkola's traditional building, whether the building is classified as good with the scale of the outer space that exists in the elements of the building's outer space.